Multisensory Cues for Encoding Urgency of System Hazards: Effect of Operator Experience on Perceived Urgency. Issue 3 (2nd October 2019) - Arrabito, G. Robert; Ho, Geoffrey; Li, Yeti; Giang, Wayne Chi Wei; Burns, Catherine M.; Hou, Ming
ABSTRACT: Objective : This study evaluated sonification and tactification for encoding urgency of system health status presented in the ground control station (GCS) visual interface of an unmanned aircraft system (UAS), and the observer's perception of urgency. Background : The barrage of data in the GCS visual interface has the potential to isolate the operator from detecting system hazards that threatens the ability of the operator to operate the UAS effectively. Method : The pitch of the UAS's engine revolutions per minute was mapped to a sonification, and excessive attitude upset of the UAS was mapped to a tactification in order to present a continuous awareness of the system's health without being invasive and obtrusive. Participants with and without flying experience were required to monitor system health, while carrying out a secondary task. Results : Regardless of flying experience, sonification enhanced hazard detection compared to a visual-only GCS interface, but tactification did not aid performance. Conclusion : While multimodal displays have been studied in remotely piloted vehicles, this is the initial effort to demonstrate that sonification can influence perceived urgency leading to greater warning compliance. Further research is warranted to develop guidelines to ensure that non-visual signals can convey different levels of urgency for a continuous awareness of a system's health, and thereby permit the operator to establish the appropriate level of priority to address the alarmed condition.